Domestic violence: women's protection - Jagbir Singh (Yking books, 2018)
Yking Books Publishers, 2018. Hardcover. Condition: New. 1st Edition. The book primarily focuses on protection of women from domestic violence Acts. The concept of service of provider is introduced in the Act for the purpose of enabling any voluntary organization to more actively and efficiently help of women protection of domestic violence. The book also light on various themes such as domestic violence and other problems of women, etc. Such reports help in reviewing the loop holes in the exciting laws and policies available for women facing domestic violence.(jacket). Seller Inventory # 128644